2013
DOI: 10.1002/bsl.2063
|View full text |Cite
|
Sign up to set email alerts
|

“Yes, I Have Sometimes Stolen Bikes”: Blindness for Norm‐Violating Behaviors and Implications for Suspect Interrogations

Abstract: Across two experiments, we studied a phenomenon akin to choice blindness in the context of participants' accounts of their own history of norm-violating behaviors. In Experiment 1, N = 67 participants filled in an 18-item questionnaire about their history of norm-violating behaviors (QHNVB). Subsequently, they were questioned about four of their answers, two of which had covertly been manipulated by the experimenter. Of the 134 manipulations, 20 (14.9%) remained undetected concurrently and 13 were accepted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 41 publications
6
37
2
Order By: Relevance
“…Furthermore, participants indicated how confident they were that this corresponded with their original rating on an 11-point scale ranging from 0 to 100%. Subsequently, as in previous studies (e.g., Johansson et al, 2005; Hall et al, 2010; Sauerland et al, 2013a, b), participants received a questionnaire to determine whether they had detected the manipulations before we disclosed that information, but refrained from revealing it while performing the task. Given that many participants were confused by the structure of the questionnaire 1 , it is doubtful whether the trials reported in the post-test questionnaire reflect genuine detections.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, participants indicated how confident they were that this corresponded with their original rating on an 11-point scale ranging from 0 to 100%. Subsequently, as in previous studies (e.g., Johansson et al, 2005; Hall et al, 2010; Sauerland et al, 2013a, b), participants received a questionnaire to determine whether they had detected the manipulations before we disclosed that information, but refrained from revealing it while performing the task. Given that many participants were confused by the structure of the questionnaire 1 , it is doubtful whether the trials reported in the post-test questionnaire reflect genuine detections.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have successfully ruled out a number of possible explanations, including poor encoding of the original (Johansson et al, 2005) or manipulated stimuli (Sauerland et al, 2013a), compliance (Johansson et al, 2005, 2008; Sauerland et al, 2013a), suggestibility or the tendency to react in socially desirable ways (Merckelbach et al, 2011; Sauerland et al, 2013a, b). However, none of these studies specifically aimed at tackling the cognitive mechanisms underlying the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some variables, like the type of decision, the manner in which the manipulation occurs, and other between-experiment variables, seem to produce different rates of blindness, choice blindness has been shown to be robust across a variety of domains. Participants' blindness rates have been remarkably high in studies of their political and moral attitudes (53 %; Hall, Johansson, & Strandberg, 2012), financial decision making (63 %;McLaughlin & Somerville, 2013), and even their reported histories of criminal and norm-violating behavior (8 %-10 %; Sauerland et al, 2013).…”
Section: Choice Blindnessmentioning
confidence: 99%